Design of the external forced air cooling control strategy for the bulb tubular turbine generator based on multi-objective optimization - Wei, Han; Zhang, Yukun; Song, Houbin; Qiu, Hongbo; Guan, Zhijun; Wang, Shuai; Xie, Wenqi (Frontiers in Energy Research, 2024)
The compact internal structure of the bulb tubular turbine generator (BTTG) leads to poor ventilation and heat dissipation capability (VHDC). It will result in high-temperature faults and lead to losses for the hydro-power station, if the staff at the hydropower station fail to promptly regulate the external forced air cooling for effective heat dissipation. Thus, a specific and effective ventilation control strategy (VCS) is of utmost importance for the operation of the BTTG. In this study, the finite element method (FEM) was employed to solve the magnetic-flow-thermal coupled field of a 24-MW BTTG. The distribution characteristics of electromagnetic losses and their impact on the temperature field were revealed. Experimental validation was conducted to verify the effectiveness of the numerical results. The response surface methodology (RSM) was employed to design an experimental plan by building upon this foundation. Integrated with a multiobjective genetic algorithm (MOGA), an optimal relationship between ambient temperature, fan flow rate, and heating components’ temperature was established. This relationship serves as the optimized ventilation control strategy for the BTTG. This research provides a theoretical framework for the formulation of operational guidelines to ensure the safe operation of generators.